A territorialização da educação agroecológica profissionalizante: uma análise crítica das narrativas e discursos de alunos e professores do IFPR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Technical and technological professional education in agroecology for rural people in Brazil began in the 2000s, although this model is recent, it is an alternative to conventional training processes based on the model of modern agriculture. The agroecological proposal is to generate transformations based on the reality of peasants, encouraging participatory construction through complex, dialogical and practical knowledge. As the training process in agroecology is under construction, it faces challenges related to internal factors such as political-pedagogical proposals; lack of institutional structures; training of the professors; and professional insertion in the professional market. Among the external challenges, the current productive development model of agribusiness stands out. Related to the presented problem, the objective of this work was to understand, since the beginning of the course in 2010, how agroecological professional education has been territorialized at IFPR. Therefore, the methodological approach used in the study is qualitative and quantitative, based on empirical data. The collection of primary data occurred through interviews with 13 professors and a questionnaire was applied to 238 students of agroecology from the following Campi: Campo Largo, Capanema, Irati and Ivaiporã. Secondary information, related to the number of agroecology courses in Brazil, was carried out online. Subsequently, the data were analyzed using Content Analysis (CA). Through spatialization by regions, there was a growth of 68.4% in agroecology courses, between 2013 and 2017, specially on the Midwest, North and Northeast Brazilian regions. With an offer of 32.7% of the total, the IFs promote capillarity and the internalization of agroecology courses in the country. At IFPR, agroecology represents only 2.5% of the institution's total courses. Based on the trajectory of the courses between 2010 and 2020, there were processes of divergences, resistance, and dropouts related to their implementation and maintenance, highlighting the complexity to implement this proposal at the institutional level. According to the students narratives, it was observed that even the agroecology course has some difficulties in social and professional recognition, they intend to seek work spaces related to the professional qualification. For professors, the agroecological professional education promoted by IFPR has managed to advance in several aspects in recent years, such as, engagement with the local and regional community. However, it still comes up against some limiting aspects, such as: the lack of an institutional guideline on agroecology, the lack of understanding of the specificities of the course, lack of material and human resources, lack of training, among others. It is concluded that, despite the challenges faced, IFPR's agroecology courses contribute to local and regional development with actions related to the collective organization of farmers, organization of marketing spaces, certification and training. Another positive factor was the creation of Study Groups in Agroecology and Organic Production (NEAs) and the development of partnerships.
Keywords: Agroecologia; Educação profissional; Territorialização; Ecologia de Saberes e Práticas; Instituto Federal do Paraná; Agroecology; Professional education; Territorialization; Ecology of Knowledge and Practices; Federal Institute of Paraná; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA